HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS MATERI BAGIAN TUBUH TUMBUHAN MELALUI PENGGUNAAN MEDIA KONKRET BERBANTUAN E-MODUL DI KELAS IV SD NEGERI KUTA PASIE - Salmiah; Intan Safiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science and Social Studies (IPAS) learning on the topic of plant body parts in elementary schools still faces the problem of low student activity and learning outcomes in Grade IV of SD Negeri Kuta Pasie. This condition is caused by the limited variety of learning media used in the classroom. Therefore, it is necessary to utilize learning media that can increase students’ involvement in the learning process. This study aims to describe students’ learning activities and learning outcomes through the use of concrete media assisted by an e-module. This research employed a qualitative approach with a descriptive type. The subjects of the study were 25 fourth-grade students of SD Negeri Kuta Pasie. Data collection techniques were conducted through observation and learning outcome tests. The observation of students’ activities included several aspects, namely paying attention, listening, completing tasks and asking questions, and showing enthusiasm in participating in the learning process. The data obtained were analyzed using descriptive qualitative analysis. The results of the study indicate that the use of concrete media assisted by an e-module can improve students’ activities in each observed aspect and provide a positive impact on students’ learning outcomes. Therefore, this learning media can be used as an alternative effective learning strategy in IPAS learning in elementary schools.